Geometrical Description of Gateroad Roof Sag - Zbigniew Lubosik; Stanislaw Prusek (International Conference on Ground Control in Mining, 2010)
"The main elements of hard coal extraction systems in the Polish mining industry, including the characteristics of gateroads, are described, followed by several dozen underground measurements of gateroad roof sag performed in different geological and mining conditions in Upper Silesia Coal Basin.Based on the analysis of the roof sag measurements, an attempt to describe the gateroad roof sag process using a geometrical model was made. To build the model, it was assumed that the roof sag curve could be described by three straight lines. The first line describes the roof sag ahead of the longwall face; the second line, the sag at the longwall-gateroad junction zone; and the last line describes the zone behind the longwall face. Determining the intersection points and inclination angles is essential for the model. These model parameters depend on the geological and mining conditions in the gateroad.Using the statistical computations and analysis, the dependencies between the characteristic points of the gateroad roof sag model and the selected geological and mining parameters were defined. The STATISTICA computer program by StatSoft was used for computation.This paper presents a simple form of the geometrical description of roadway roof sag progression that is very useful during the gateroad support design process.INTRODUCTIONThe longwall system with caving is the dominant method in European mining in cases of hard coal seam extraction. For instance, in Poland, in 2009, 117 longwalls were driven, with total production of 77.5 million tonnes. In roughly 95% of the longwalls, mining operations were conducted using longwalls with roof caving; the remaining 5% used the hydraulic stowing system. The average mining depth was about 700 m (2,297 ft), and average daily output per face was approximately 2,600 tonnes per day. When using the longwall mining system, gateroads play an important role. These principal roadways transport materials, mine crews, and output. In addition, they impact ventilation of the extraction area, affecting, among other things, the climatic conditions or methane hazard. Unfortunately, difficulties often appear in maintaining an adequate size for the gateroads, due to the face line, which causes origination zones with stress concentration around the gateroad, resulting in rock mass movements in the form ofroofsag, floor heave, or horizontal convergence (Figure 1)."